All Days 2011
DOI: 10.2118/144357-ms
|View full text |Cite
|
Sign up to set email alerts
|

Practical Aspects of Reserve Determinations for Shale Gas

Abstract: Shale gas currently provides 20% of domestic supply, is targeted by half of the gas-directed drilling rigs, and represents the large majority of domestic resources. However, modern shale plays, their development strategies and their engineering analysis are young by comparison to those of conventional reservoirs. Uncertainty in shale gas reserves has significant implications at both the micro and macro levels.Conventional reservoir engineering tools must be viewed as potentially inadequate (or even inappropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Despite the common practice in shale modeling using a conventional approach, which is usually done at the well level (Strickland et al, 2011), this technique is capable of performing history matching for all individual wells in addition to full field by taking into account the effect of offset wells.…”
Section: Top-down Modeling E Pattern Recognition Based Reservoir Modementioning
confidence: 99%
“…Despite the common practice in shale modeling using a conventional approach, which is usually done at the well level (Strickland et al, 2011), this technique is capable of performing history matching for all individual wells in addition to full field by taking into account the effect of offset wells.…”
Section: Top-down Modeling E Pattern Recognition Based Reservoir Modementioning
confidence: 99%
“…By 2000, production rates increased somewhat to approximately 0.8 Bscf/D. However, in the subsequent decade, rates rapidly increased, and production rates amounted to 10 Bscf/ D in 2010 (Sutton et al 2010). The US Energy Information Administration forecasts that US shale-gas production will exceed 37 Bscf/D in 2035.…”
Section: Introductionmentioning
confidence: 98%
“…The US Energy Information Administration forecasts that US shale-gas production will exceed 37 Bscf/D in 2035. 1 The number of wells producing shale gas increased from 500 to more than 12,000 from 1995 to 2010 (Sutton et al 2010). Although the impact of unconventional gas in the US has been enormous, opinions are divided on the question as to what degree this success can be replicated outside the US (Martin 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of rate-transient analysis, formulations were not initially available to handle the physical geometry of the completions. Simulation is more flexible, but there is significant uncertainty as to the nature of the resulting completion, production mechanisms and how to model these [Strickland et al, 2011]. Studies have shown that Darcy flow and instantaneous capillary equilibrium applied in simulators for conventional reservoirs are inadequate for reliable simulation of shale gas reservoirs [Andrade et al, 2010].…”
Section: Problem Descriptionmentioning
confidence: 99%